2018
DOI: 10.3389/fneur.2018.00451
|View full text |Cite
|
Sign up to set email alerts
|

Extended Erythropoietin Treatment Prevents Chronic Executive Functional and Microstructural Deficits Following Early Severe Traumatic Brain Injury in Rats

Abstract: Survivors of infant traumatic brain injury (TBI) are prone to chronic neurological deficits that impose lifelong individual and societal burdens. Translation of novel interventions to clinical trials is hampered in part by the lack of truly representative preclinical tests of cognition and corresponding biomarkers of functional outcomes. To address this gap, the ability of a high-dose, extended, post-injury regimen of erythropoietin (EPO, 3000U/kg/dose × 6d) to prevent chronic cognitive and imaging deficits wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 80 publications
(115 reference statements)
1
16
1
Order By: Relevance
“…Both groups performed at equivalent levels during reversal sessions when performance was low and perseveration high (i.e., <50%), while HIE mice committed more trials and errors during sessions when performance was largely learning related (i.e., >50%). This deficit is in contrast to previously published touchscreen assessments in animal models of perinatal brain injury (38,41,57). Specifically, adult rats perinatal brain injury secondary to chorioamnionitis have a perseverative phenotype and significant deficit in cognitive control defined by a reversal deficit (38).…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Both groups performed at equivalent levels during reversal sessions when performance was low and perseveration high (i.e., <50%), while HIE mice committed more trials and errors during sessions when performance was largely learning related (i.e., >50%). This deficit is in contrast to previously published touchscreen assessments in animal models of perinatal brain injury (38,41,57). Specifically, adult rats perinatal brain injury secondary to chorioamnionitis have a perseverative phenotype and significant deficit in cognitive control defined by a reversal deficit (38).…”
Section: Discussioncontrasting
confidence: 77%
“…Specifically, adult rats perinatal brain injury secondary to chorioamnionitis have a perseverative phenotype and significant deficit in cognitive control defined by a reversal deficit (38). Similarly, adult rats suffering severe traumatic brain injury in infancy perseverate, lack cognitive flexibility and struggle to pass reversal learning criteria (41). The extensive white matter brain injury and orbitofrontocortical decoupling observed in both chorioamnionitis and traumatic brain injury may partially explain these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 20 years, erythropoietin (EPO) has emerged as a potential candidate for neuroprotective and neuroregenerative treatment in injury and disease of the nervous system (Sargin et al, 2010 ). Interestingly, EPO improves cognitive performance in healthy animals and humans and in disease, including in MS (Ehrenreich et al, 2007 ; Robinson et al, 2018 ; Li et al, 2018 ). Although the mechanism is still largely unknown, we and others showed that EPO acts directly on OLs to increase myelination in vitro and in vivo (Sugawa et al, 2002 ; Cervellini et al, 2013 ; Hassouna et al, 2016 ; Gyetvai et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, DTI-MRI has been used as read-out of treatment efficacy in rodents' models of TBI. In particular, DTI has revealed the beneficial effect on white matter integrity of activation of mitochondrial calcium fluxes (Parent et al, 2020 ), of autophagy modulators (Medina et al, 2017 ; Yin et al, 2018 ), estrogens (Kim et al, 2015 , 2017 ), metamphetamine (Ding et al, 2013 ), erythropoietin (Robinson et al, 2016 , 2018 ), tissue plasminogen activator (in mice; Xia et al, 2018 ), mGluR5 (in mice; Byrnes et al, 2012 ), and dietary modulations (Shultz et al, 2015 ; Schober et al, 2016 ; Tan et al, 2016 ). Notably, the detrimental effect of alcohol in TBI was also investigated by DTI (Kong et al, 2013 ).…”
Section: Applications To Models Of Neurodegenerative Diseasesmentioning
confidence: 99%